PENGARUH VARIASI CAMPURAN KAYU PINUS TERHADAP KINERJA GASIFIKASI SEKAM PADI MENGGUNAKAN UPDRAFT GASIFIER - , TUNJUNG BAYU HERNAWAN; , Dr. Ir. Bambang Purwantara, M.Agr. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Gasification is a technology for convert solid biomass into energy in the form of gas . The research was conducted to determine the effect of variations in the mix of pine wood gasifier performance. Gasifier performance is the rate of decrease in material, the temperature of the stove , the temperature of the reactor , the volume of tar, the rest mass gasification and effective flame. The research was conducted with a mixture of pine wood variation of 0% , 5% , 10% , 15% and 20%. and the results compared with the variation of a mixture of 0 % at a load of 10 kg and 20 kg. To determine the effect of treatment on the performance parameters of statistical analysis used to test the method factorial completely randomized design and Duncan test. The results showed that the variation of a mixture of pine wood can improve performance of gasifier. Based on factorial analysis and Duncan test, a mixture of 15% pine wood gasifier can improve performance in terms of reactor temperature, flame effectively, and the volume of tar and a mixture of 20% can improve the performance in terms of the temperature of the stove because it has almost the same performance with a load of 10 kg and 20 kg in the mixture 0%. The addition of a mixture of pine wood not able to improve performance of the gasifier is optimal in terms of mass combustion and the rate of decrease in material. Key words: Gasification, performance, mixture , rise husk, pine wood